Inculcation And Replication Of Values In An Organizational Setting: The Case Of Kiit’s Stakeholders - et. al., Pragyan Ranjan Gharai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the study is to gain a better understanding of how social entrepreneurial leadership and non-profit motive of the founder of KIIT has not only created social values, but also attracted the like-minded stakeholders to join the organization and inculcate its organizational culture and values in a unique manner. The study based on a sample of 200 respondents taken from among the stakeholders on the basis of purposive as well as convenience sampling reveals that the attempt made by KIIT to embed its organizational culture and values in the employees’ mind has been successful to such an extent that the replication of the same are evinced in the gestures shown by the employees after being imbued with the culture and values of KIIT and KISS. All these have been possible due to the selfless and untiring efforts of the visionary founder of KIIT and KISS.